2019
DOI: 10.1111/1467-9566.13006
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the pharmaceuticalisation of pandemic influenza using Lukes’ framework of power

Abstract: The power of social actors to drive or block pharmaceutical uptake has been a concern in sociological debates on pharmaceuticalisation, including in the case of pandemic vaccination. We build on Steven Lukes' three-dimensional view of power to explore the 2009 H1N1 pandemic vaccination in Sweden and Denmarktwo similar countries that arrived at conflicting vaccination strategies. Drawing on interviews with members of each country's pandemic steering group and on document analysis, we explore three consecutive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…In a recent article, Mulinari and Vilhelmsson (2020) showed how Sweden, and particularly the Public Health Agency of Sweden, managed the 2009 H1N1 (swine flu) pandemic. Sweden differed from other countries in the management of that pandemic as well.…”
Section: Swedish Management Of Previous Pandemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent article, Mulinari and Vilhelmsson (2020) showed how Sweden, and particularly the Public Health Agency of Sweden, managed the 2009 H1N1 (swine flu) pandemic. Sweden differed from other countries in the management of that pandemic as well.…”
Section: Swedish Management Of Previous Pandemicsmentioning
confidence: 99%
“…Both then and in the current situation, the Swedish government and expert authorities focused on recourses and communication to protect risk groups and fundamental societal structures. Mulinari and Vilhelmsson (2020) showed that these measures were achieved in 2009 by encouraging people's solidarity with vulnerable people, and they argue that high levels of trust in institutions and the health care system support the process. Furthermore, mass media worked together with expert authorities and the government to create a strong alliance in 2009 that promoted mass vaccination for the common good, even though it meant downplaying that the vaccination only benefitted a minority of the population and might even harm some individuals.…”
Section: Swedish Management Of Previous Pandemicsmentioning
confidence: 99%
“…In 2009, during the H1N1 (swine flu) outbreak, Denmark only vaccinated risk-groups whereas Sweden pursued mass vaccination. In a previous research project, we compared Sweden’s and Denmark’s contrasting pandemic response focusing on pharmaceutical interventions in terms of vaccination (Mulinari and Vilhelmsson, 2020) and antiviral strategies (Vilhelmsson and Mulinari, 2018).…”
Section: Déjà Vumentioning
confidence: 99%
“…i den studie av vaccineringen mot svininfluensan 2009 i Danmark och Sverige som jag nyligen var med om att genomföra (Mulinari & Vilhelmsson 2020), såg vi exempelvis hur en stark konsensus innebar att grundläggande konflikter osynliggjordes. Barn vaccinerades en masse för att stoppa spridningen av influensan, vilket de facto utsatte dem för en medicinsk risk.…”
Section: Shai Mulinariunclassified
“…Studier av vaccinationsstrategier i europa under pandemin 2009 visade exempelvis att många länder faktiskt följde sina respektive experter och myndigheters råd men att dessa råd kunde skilja sig kraftigt åt mellan länderna (Baekkeskov 2016;Mulinari & Vilhelmsson 2020). Till exempel rekommenderade den svenska pandemigruppen att Sverige skulle genomföra massvaccination -ett råd som den svenska regeringen följde.…”
Section: Shai Mulinariunclassified